Frequency of mutations in PRKN, PINK1, and DJ1 in Patients With Early-Onset Parkinson Disease from neighboring countries in Central Europe. (May 2021) - Milanowski, Łukasz M.; Lindemann, Jennifer A.; Hoffman-Zacharska, Dorota; Soto-Beasley, Alexandra I.; Barcikowska, Maria; Boczarska-Jedynak, Magdalena; Deutschlander, Angela; Kłodowska, Gabriela; Dulski, Jarosław; Fedoryshyn, Lyuda; Friedman, Andrzej; Jamrozik, Zygmunt; et al.
Abstract: Introduction: Approximately 10% of patients with Parkinson disease (PD) present with early-onset disease (EOPD), defined as diagnosis before 50 years of age. Genetic factors are known to contribute to EOPD, with most commonly observed mutations in PRKN, PINK1, and DJ1 genes. The aim of our study was to analyze the frequency of PRKN, PINK1, and DJ1 mutations in an EOPD series from 4 neighboring European countries: Czech Republic, Germany, Poland, and Ukraine. Methods: Diagnosis of PD was made based on UK Brain Bank diagnostic criteria in departments experienced in movement disorders (1 from Czech Republic, 1 from Germany, 9 from Poland, and 3 from Ukraine). EOPD was defined as onset at or before 50 years of age. Of the 541 patients recruited to the study, 11 were Czech, 38 German, 476 Polish, and 16 Ukrainian. All cohorts were fully screened with Sanger sequencing for PRKN, PINK1, and DJ1 and multiplex ligation-dependent probe amplification for exon dosage. Results: PRKN homozygous or double heterozygous mutations were identified in 17 patients: 1 Czech (9.1%), 1 German (2.6%), 14 Polish (2.9%), and 1 Ukrainian (6.3%). PINK1 homozygous mutations were only identified in 3 Polish patients (0.6%). There were no homozygous or compound heterozygous DJ1 mutations in analyzed subpopulations. One novel variant in PRKN was identified in the Ukrainian series. Conclusion: In the analyzed cohorts, mutations in the genes PRKN, PINK1, and DJ1 are not frequently observed. Highlights: Approximately 10% of patients with PD present with early-onset disease. PRKN, PINK1, and DJ1 were screened in Czech, German, Polish, and Ukrainian patients. PRKN, PINK1, and DJ1 are a rare cause of EOPD in central Europe.